Indonesia's Dispute Against the European Union Related to The Nickel Ore Export: WTO Case Analysis - Dinar Al Qadri; Suarni Sonda; Muhammad Fadly Saleh; Eddy Pelupessy; Thresia Hilda Mathelda Yenkase (Universitas Negeri Semarang, 2025)
The purpose of this study is to examine the basis of the World Trade Organization (WTO) decision in favor of the European Union over Indonesia in the case of a ban on nickel ore exports by the Government of Indonesia and the appeal efforts that can be taken by the Indonesian government against the decision. This study uses normative legal research methods with conceptual and statutory approaches. The results of the study show that the basis of the WTO ruling in favor of the European Union over Indonesia in the case of the Indonesian Government's Nickel Seed Export Ban is that the Nickel Processing and Refining policy in Indonesia is proven to violate the provisions of WTO Article XI.1 GATT 1994 and cannot be justified by Articles XI.2 (a) and XX (d) GATT 1994. Indonesia is also deemed to be conducting a prohibited subsidy scheme under Subsidy and Countervailing Measures Agreement Article 3.1 through Minister of Finance Regulation (PMK) No. 76 Year 2012. The appeal has been taken by the Indonesian government officially in December 2022 and is still waiting for the formation of the WTO Appellate Body. Indonesia has a great opportunity to win a dispute at the WTO if Indonesia can prove the existence of national laws governing international trade, especially in the mining sector.